On-Load Tap-Changer with Surge Arresters - Hallmans, Oskar (My University, 2024)
Hitachi Energy are advancing the world’s energy systems to be more sustainable, flexible and secure by offering solutions for distributing electricity over large distances. A key component in the electrical grid are transformers and their transformation of electrical energy between voltage levels. An important component of the transformer is the On-Load Tap-Changer (OLTC). It makes it possible to ensure a sufficiently stable voltage level on the power grid, by alternating the number of turns in the transformer winding. Quality assurance and safety is of essence since transformer failures can have huge consequences, therefore a safety device so-called surge arrester can be used to protect the OLTC from over-voltages from the grid that may occur and direct them to ground. However, another tap-changer model in Hitachi Energy’s product range lacks this feature due to space limitations within the tap-changer compartment. The aim with this thesis is to make a concept design with surge arresters for the model that does not have this feature yet. During the project, a problem definition was stated and a prestudy performed in combination with the establishment of a requirements specification to find a solution to the problem. An iterative process of concept generation, design reviews and concept selection methods was done to end up with a final design. The final design was then 3D-printed to demonstrate the solution. The final design consists of three holders that holds the surge arresters in place, the surge arresters has been modified with a groove and new connectors that connects the surge arresters electrically through connection plates to the diverter switch. This concept fulfils all requirements and wishes that has been possible to evaluate during the thesis and serves as a foundation for future work for Hitachi Energy.